Excellent Service and Patient Satisfaction in Health Clinic Services - Priyantini, Diah; Marini, Gita; Ulfa, Ariana; Uliyah, Musrifatul (Fundamental and Management Nursing Journal, 2023)
Introduction: The application of excellent service has been widely implemented in the clinical setting. Excellent service consists of attitude, appearance, attention, action and accountability that should behave by health professionals including nurse. This study aims to analyze the relationship between excellence service and patient satisfaction at the health clinics in Indonesia. Method:This research is a correlational study with a cross sectional approach. The population of this study was 500 respondents at the Health Clinic. The sampling technique used simple random sampling and obtained a sample of 372 respondents. The independent variable in this study is service excellent and the dependent variable is patient satisfaction. Data analysis used in this study used Spearman's rho with a significant value <0.05. Results: A total of 209 respondents stated excellent with 25 stating very satisfied, 179 satisfied and 5 less satisfied. A total of 64 patients stated that they were not excellent with 5 satisfied respondents and 59 unsatisfied respondents. Based on the Spearman rho test (p = 0.000) it shows that there is a relationship. Conclusion: This study revealed a significant relationship between service excellence and patient satisfaction. Implementing excellent service at the Health Clinic by numbering form, implementing online queues and increasing quality human resources is promising. This practice not only benefited patients as the customer but also health clinics as health provider.